2012
DOI: 10.1155/2012/413589
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Chemoradiation in Squamous Cell Carcinoma of the Maxillary Sinus: A 26-Year Experience

Abstract: Background. The aim of our study was to evaluate the effects of neoadjuvant platinum-based radiochemotherapy (RCT) in patients with maxillary sinus squamous cell carcinoma and to compare the results with other multimodality treatment concepts for advanced-stage maxillary sinus carcinoma in the literature. Methods. In total, 53 patients with squamous cell carcinoma of the maxillary sinus were reviewed retrospectively. All patients received a neoadjuvant RCT containing either cisplatin or carboplatin followed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 60 publications
(65 reference statements)
1
16
0
Order By: Relevance
“…Some groups have reported no significant difference in survival outcomes when comparing patients who underwent surgery plus adjuvant RT with patients who received definitive RT . Other investigators have also highlighted the benefit of neo‐adjuvant RT and CRT …”
Section: Discussionmentioning
confidence: 99%
“…Some groups have reported no significant difference in survival outcomes when comparing patients who underwent surgery plus adjuvant RT with patients who received definitive RT . Other investigators have also highlighted the benefit of neo‐adjuvant RT and CRT …”
Section: Discussionmentioning
confidence: 99%
“…This point highlights the weaknesses of the TNM classification: the TNM classification does not consider molecular characteristics that may predict response to neoadjuvant chemoradiation protocols and new molecular therapeutic approaches, such as targeted therapy . For advanced‐stage maxillary sinus cancer, however, multimodal treatment regimes containing neoadjuvant chemoradiation have proven to be effective . To incorporate therapeutic approaches other than surgery, the TNM system has to be stratified by therapy.…”
Section: Discussionmentioning
confidence: 99%
“…26 For advanced-stage maxillary sinus cancer, however, multimodal treatment regimes containing neoadjuvant chemoradiation have proven to be effective. 27,28 To incorporate therapeutic approaches other than surgery, the TNM system has to be stratified by therapy. This leads to an exponential increase in stage groups making it very difficult to evaluate the results because of the small number of patients in every stage group.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, clinical studies have demonstrated that radiotherapy combined with chemotherapy (Ang et al, 2010), especially based on single-agent cisplatin (Segawa et al, 2010;Kreppel et al, 2012) is superior to radiotherapy alone. However, because platinum drugs usually target DNA, differences in the ability to repair DNA are often the direct cause for the observed differences in sensitivity to platinum drugs among patients (Kiyohara et al, 2006).…”
Section: Introductionmentioning
confidence: 99%